2020
DOI: 10.1101/2020.04.05.20053819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma Metabolomic and Lipidomic Alterations Associated with COVID-19

Abstract: The pandemic of the coronavirus disease 2019 has become a global public health crisis. The symptoms of COVID-19 range from mild to severe conditions. However, the physiological changes associated with COVID-19 are barely understood.In this study, we performed targeted metabolomic and lipidomic analyses of plasma from a cohort of COVID-19 patients who had experienced different symptoms. We found the metabolite and lipid alterations exhibit apparent correlation with the course of disease in these COVID-19 patie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
97
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 27 publications
11
97
2
2
Order By: Relevance
“…Changes in primarily polar metabolites among COVID-19 patient cohorts from China, Italy, and France have been reported. [9][10][11][12] In agreement with those studies, we observed a dysregulation of amino acid pools, interruption of the glucose to lactate balance, and dysregulation of nucleotide catabolic products such as xanthine, hypoxanthine, and urate (Sup. Fig.…”
Section: Main Textsupporting
confidence: 91%
See 1 more Smart Citation
“…Changes in primarily polar metabolites among COVID-19 patient cohorts from China, Italy, and France have been reported. [9][10][11][12] In agreement with those studies, we observed a dysregulation of amino acid pools, interruption of the glucose to lactate balance, and dysregulation of nucleotide catabolic products such as xanthine, hypoxanthine, and urate (Sup. Fig.…”
Section: Main Textsupporting
confidence: 91%
“…[4][5][6] While several studies have examined the systemic metabolic correlates of COVID-19, a well resolved interrogation of the lipidomic changes in COVID-19 severity has not been pursued. [9][10][11][12] To measure lipidomic changes in COVID-19 and gain mechanistic insights into how these changes may drive disease severity, we used serum draws from 19 healthy patients (healthy), 18 COVID-19 patients who did not require ICU admission (moderate) and 20 patients that required ICU admission (severe). The demographics, preexisting conditions, and treatment details of these patients are indicated in Table 1.…”
Section: Main Textmentioning
confidence: 99%
“…Previous studies have found that lipid metabolism impairment may involve in the pathogenesis of sepsis secondly to pneumonia and in uenza [10][11][12]. Similarly, recent studies observed the dyslipidemia in the patients infected with SARS-CoV-2 by MS analysis, especially in the severe cases [7][8][9], which reminded us that blood lipid might serve as a maker for the severity of COVID-19. While among the altered lipids, ApoA1 was very obviously decreased.…”
Section: Discussionmentioning
confidence: 77%
“…Consequently, some clinical characteristic, in ammation index and cytokines have been used as markers to re ect the severity of COVID-19 by us and others [5,6]. Recently, emerging evidence suggested that lipid metabolism dysregulation may involve into the progression of COVID-19 revealed bymass spectrometry (MS)-based proteomics analysis [7][8][9]. Although MS analysis is not common performed, blood lipid is routinely examined by automatic biochemical instrument in clinically laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…For example, meta-transcriptome sequencing was conducted on the bronchoalveolar lavage uid of SARS-CoV-2 infected patients 18 . Proteomic and metabolomic analyses of the serum from COVID-19 patients have also been investigated [19][20][21] . However, from the data so far, it remains di cult to determine which parameters are due to infection from the virus and which to comorbidities as no systematic study of the disease have been published thus far.…”
Section: Introductionmentioning
confidence: 99%